Significant Different Level of Malondialdehyde (MDA) as Oxydative Stress Marker in Severity Groups of Acne Vulgaris - Sylvia Anggraeni; Trisniartami Setyaningrum; M Yulianto Listiawan (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2017)
Background: Acne vulgaris (AV) is a common chronic inflammatory disease of sebaceous gland that may decrease patient’s quality of life. Oxidative stress is suggested to play role in the pathogenesis of AV. Purpose: To evaluate the differences of malondialdehyde (MDA) level as oxidative stress marker in AV severity. Method: This is an analytic observational cross sectional research of AV patients in Cosmetic Division of Dermatology and Venereology Outpatient Clinic of Dr. Soetomo hospital Surabaya. Subjects were collected through consecutive sampling since May-August 2015. Total samples were 42 patients, classified into 3 severity groups (mild, moderate, severe).  Samples were taken from blood vein, examined with Enzyme-linked immunosorbent assay (ELISA) then analyzed statistically. Results: There were differences of MDA mean level among AV severity groups: mild 58.371 ng/ml (SD±25.2141); moderate 99.121 ng/ml (SD±8.5172); and severe 171.779 ng/ml (SD±49.9694). Post hoc analytic revealed that there were statistically differences of MDA level in all stages (mild-moderate p=0.002; mild-severe p=0.000; moderate-severe p=0.000). Conclusions: This research revealed that oxidative stress plays a role in AV pathogenesis. Lipid peroxidation process in sebum produced lipid oxidant that could induce inflammatory process in sebaseous gland via Peroxisome Proliferator-Activated Receptor  (PPAR).